TINGKAT PENGEMBALIAN KREDIT NASABAH UPKD DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (Studi di Desa Pagar Agung Kecamatan Seluma Barat Kabupaten Seluma) - Maryono, . (Jurnal AGRISEP, 2007)
This research aimed to know the rate of return credit from costumers of Pagar Agung UPKD and to know the factors which influence the rate of return credit from the costumer of Pagar Agung UPKD by using primary and secondary data. Data was taken from 35 sample of costumers by using “purposive”. The statistic analisis which been used in this research was multiple linier regression by using one tail of t-test with confidence level of 95 % (? = 0,05) and f-test with confidence level 95 % (? = 0,05). The result of research showed that the rate of return credit highly varied according to the costumers ability and willingess The result of research by using multiple linier regression showed that on the confidence level of 95 % the long term to be costumers, household income, amount of family respon sibility,  education, level of credit were influential significantly, whereas the variable of, age, consumtion and work status were not influential significantly toward the credit rate ot return. Key word : Credit, Rate of Return, Costumers.